Religious Coping and Health-promoting Lifestyle Among Iranian Infertile Women - Amin Gheysari; Marhamat Farahaninia; Seyedeh Batool Hasanpoor-Azghady (Iran University of Medical Sciences, 2023)
Background: Infertility is recognized as a stressful and critical experience worldwide and across cultures and disrupts individual, marital, family, and social stability. Religion serves as a source of support in dealing with health-related problems. This study investigates the relationship between religious coping mechanisms and health-promoting lifestyle (HPL) among Iranian infertile women. Methods: A cross-sectional correlational study was conducted on 177 infertile women referring to the Sarem Sub-specialized Infertility Treatment and Research Center in Tehran City, Iran, 2019. The subjects were recruited by continuous sampling. The data in this study were collected using a demographic information form, the Iranian religious coping scale (IRCS), and the health-promoting lifestyle profile-II (HPLP-II). Statistical analyses, including the independent t-test, one-way ANOVA, and Pearson correlation coefficient, were performed using SPSS software, version 22. The significance level was set at P<0.05. Results: The highest mean was related to active religious coping (7.86±2.39), while passive religious coping (2.89±1.76) and negative feelings towards God (3.95±2.07) had the lowest mean scores. The Mean±SD score of health-promoting lifestyle was 128.34±13.46; the score range was 52-208, lower than the median score of the scale. A weak but significant inverse relationship was observed between negative feelings towards God and HPL (r=-0.19; P=0.013) and its three subscales: Physical activity (r=-0.18; P=0.019), nutrition (r=-0.21; P=0.011), and interpersonal relationships (r=-0.21; P=0.01). Also, a weak yet statistically significant inverse association was observed between passive religious coping and interpersonal relations (r=-0.18; P=0.029). Conclusion: Considering that the mean HPL score of infertile women was lower than the median score of the scale, community-oriented education and care programs are recommended to improve HPL in infertile women. Teaching and strengthening positive/active religious coping strategies to improve HPL are also advised.